Cholesterol metabolism and its relation to the brain?s acetylcholinesterase homeostasis: a preclinical study - Barros, Wellinghton de Medeiros (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Biológicas, Programa de Pós-Graduação em Neurociências, Florianópolis, 2022.